Economic feasibility and the energetic potential from landfill gas in Campinas - SP (Research, Society and Development, 2019)
The need in the use of renewable energy added to the problem of collection and final disposal of Municipal Solid Waste (MSW) in large urban areas shows the importance of the correct management of this waste. In this context, the use of the gases generated from the degradation of these wastes is essential. In the present work an estimation is made for the biogas production as well as the economic feasibility of the use of the s biogas generated in a landfill and a composting yard sized for the city of Campinas - SP, between the years of 2018 and 2038. Landfill Gas Emissions Model (LandGEM) and the Waste Reduction Model were used to estimate the greenhouse gases (GHG) emissions. Three scenarios were analyzed using the WARM method and scenario 3 was the one that presented the greatest GHG emission reduction and the second-best scenario in terms of energy consumption. Also, the LandGEM estimated the production of methane (CH4), carbon dioxide (CO2) and other gases. The amount of biogas generated for the 20 years of production was 934,872,000 m3, corresponding to the life of the landfill. The study shows that an installed power of 4MW results in the installation of a financially viable enterprise to generate electricity with different dolar values that varies between R$2.80 to R$5.80. In addition, the environmental advantages are the reduction in GHG emissions and the contribution to an effective management of municipal solid waste in large urban areas.